Grazing intensity alters the plant diversity–ecosystem carbon storage relationship in rangelands across topographic and climatic gradients. (26th January 2023) - Sanaei, Anvar; Sayer, Emma J.; Yuan, Zuoqiang; Saiz, Hugo; Delgado‐Baquerizo, Manuel; Sadeghinia, Majid; Ashouri, Parvaneh; Ghafari, Sahar; Kaboli, Hasan; Kargar, Mansoureh; Seabloom, Eric W.; Ali, Arshad
Abstract: Plant diversity supports multiple ecosystem functions, including carbon sequestration. Recent shifts in plant diversity in rangelands due to increased grazing pressure and climate changes have the potential to impact the sequestration of carbon in arid to semi‐humid regions worldwide. However, plant diversity, grazing intensity and carbon storage are also influenced by environmental factors such as nutrient availability, climate and topography. The complexity of these interactions limits our ability to fully assess the impacts of grazing on biodiversity–ecosystem function (BEF) relationships. We assessed how grazing intensity modifies BEF relationships by determining the links between plant diversity and ecosystem carbon stocks (plant and soil carbon) across broad environmental gradients and different plant growth forms. To achieve this, we surveyed 1493 quadrats across 10 rangelands, covering an area of 23, 756 ha in northern Iran. We show that above‐ground carbon stocks increased with plant diversity across topographic, climatic and soil fertility gradients. The relationship between above‐ground carbon stocks and plant diversity was strongest for forbs, followed by shrubs and grasses. Soil carbon stocks increased strongly with soil fertility across sites, but aridity, grazing, plant diversity and topography were also important in explaining variation in soil carbon stocks. Importantly, above‐ground and soil carbon stocks declined at high grazing intensity, and grazing modified the relationship between plant diversity and carbon stocks regardless of differences in abiotic conditions across sites. Our study demonstrates that relationships between plant diversity and ecosystem carbon stocks persist across gradients of aridity, topography and soil fertility, but the relationships are modified by grazing intensity. Our findings suggest that potential losses in plant diversity under grazing intensification could reduce ecosystem carbon storage across wide areas of arid to semi‐humid rangelands. We discuss the potential mechanisms underpinning rangeland BEF relationships to stimulate future research. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.